Effects of IL6 C‐634G polymorphism on tooth loss and their interaction with smoking habits. (14th July 2015) - Suma, S; Naito, M; Wakai, K; Sasakabe, T; Hattori, Y; Okada, R; Kawai, S; Hishida, A; Morita, E; Nakagawa, H; Tamura, T; Hamajima, N
<x xml:space="preserve">Abstract</x> Objective To examine the association between an IL6 (Interleukin‐6) polymorphism (C‐634G or rs1800796) and tooth loss, and an interaction between the polymorphism and smoking habits for the loss. Material and Methods Our subjects were 4917 check‐up examinees ages 35–69. They reported tooth loss and lifestyle in a questionnaire. We regressed the number of teeth on the IL6 genotype, gender, age, smoking, drinking, diabetes, hypertension, physical activity, energy intake, education, and brushing. We further estimated multivariate‐adjusted odds ratios (ORs) for having <20 teeth. Results Participants with a GG genotype tended to have less teeth than those with CC; β = −0.798 (95% confidence interval [CI] = −1.501–−0.096). Subjects with a GG genotype were more likely to have <20 teeth than those with CC; OR was 1.56 (95% CI = 1.08–2.25). Association between current smoking and tooth loss was stronger among those with GG than among those with CC. In a multiple regression analysis, a significant interaction was found between GG genotype and current smoking in the prediction of tooth loss (P = 0.018). Conclusion The IL6 C‐634G polymorphism was significantly associated with tooth loss. Our results suggest greater effects of smoking on tooth loss in GG genotype individuals.